A small-molecule probe for monitoring binding to prolyl hydroxylase domain 2 by fluorescence polarisation. Issue 91 (28th October 2020) - Li, Zhihong; Zhen, Shuai; Su, Kaijun; Tumber, Anthony; Yu, Quanwei; Dong, Ying; McDonough, Michael; Schofield, Christopher J.; Zhang, Xiaojin
Abstract : A small-molecule FP probe useful for monitoring binding to PHD2 and identifying potential PHD2 inhibitors. Abstract : Inhibition of the dioxygen sensing hypoxia-inducible factor prolyl hydroxylases has potential therapeutic benefit for treatment of diseases, including anaemia. We describe the discovery of a small-molecule probe useful for monitoring binding to human prolyl hydroxylase domain 2 (PHD2) via fluorescence polarisation. The assay is suitable for high-throughput screening of PHD inhibitors with both weak and strong affinities, as shown by work with clinically used inhibitors and naturally occurring PHD inhibitors.